Village Governance and Public Participation in Indonesia - Putra, Fadillah (Journal of Interdisciplinary Socio-Economic and Community Study, 2023)
Village Law in Indonesia explicitly mandates village governments to fundamentally promote public participation and empowerment. This study aims to evaluate Village Fund Program from the perspective of community-led development. Based on Arnstein's ladder of participation and in-depth interview method, this research found out that village community participation in the government and development system was at the level of tokenism. Village governments do provide an opportunity for the public to participate in the development planning forum, but public aspirations were not guaranteed to be converted into concrete policies. In terms of community empowerment, village governments merely implemented one of the five main principles of community-led development.